Lecture two: The evolution of morality: The emergence of personhood - J. Wentzel van Huyssteen (HTS Teologiese Studies/Theological Studies, 2017)
In a series of three articles, presented at the Goshen Annual Conference on Science and Religion in 2015, with the theme ‘Interdisciplinary Theology and the Archeology of Personhood’, J. Wentzel van Huyssteen considers the problem of human evolution – also referred to as ‘the archaeology of personhood’ – and its broader impact on theological anthropology. This trajectory of lectures tracks a select number of challenging contemporary proposals for the evolution of crucially important aspects of human personhood. Lecture Two argues that, on a postfoundationalist view, some of our religious beliefs are indeed more plausible and credible than others. This also goes for our tendency to moralise and for the strong moral convictions, we often hold. It demonstrates that, in spite of a powerful focus on the evolutionary origins of moral awareness, ethics emerge on a culturally autonomous level, which means that the epistemic standing of the particular moral judgements human beings make is independent of whatever the natural sciences can says about their genesis.